ANALISIS INPUT- OTPUT PADA SEKTOR TRANSPORTASI DI INDONESIA - Surti, Surti (Scientific : Jurnal Ilmu-Ilmu Sosial dan Ekonomi, 2020)
The transportation sector plays an important role in the development of other economic sectors in a country. Because of this vital role, this research tries to find out how much influence the development of the transportation sector has on other sectors, so that it can provide an overview of policy directions for the relevant government.The transportation sector is one of the sectors that has the highest growth rate in addition to the corporate services sector and the health and social activities sector. By using the 2010 economic sector input output approach, this study finds that the 5 subsectors that have a high total backward linkage index are rail transportation, land transportation, sea transportation, river transportation, lakes, and transportation. times, warehousing and transportation support services. This shows that the transportation sector is able to attract and develop the upstream sector.However, based on the results of future linkages, the 6 transportation sub-sectors all have a low total index with a value of < 1. This indicates that the transportation sector has not been able to boost output in the downstream sector. This can happen because the development of transportation infrastructure is only focused on the islands of Java and Sumatra, so that the transportation sector is not fully developed and tends to be concentrated in certain areas. The results of the multiplier analysis of income and employment of all transportation sub-sectors have low values. The low value of the multiplier of income and employment in each sub-sector indicates that a decrease in the budget of each transportation sub-sector has a relatively low impact on society and household income or employment.